Uncovering multilevel drivers of cancer disparities among Latinos in the United States - Amelie G. Ramirez; Edgar Munoz; Lorna Rodriguez-Rodriguez; Leon Bernal-Mizrachi; Jose Aron Lopez; Paulo S. Pinheiro; Barbara Segarra-Vasquez; Gregory Talavera; Luis G. Carvajal-Carmona; Adolfo Diaz Duque; Cliff Despres; Edward J. Trapido (Frontiers in Public Health, 2025)
Cancer disparities among Latinos in the United States persist as a significant public health challenge, characterized by inequitable outcomes throughout the cancer continuum. Latinos experience elevated rates and poorer prognoses in certain cancers compared to other populations, driven by complex, multilevel interactions involving environmental exposures, genetic factors, cultural practices, and systemic inequalities. Recognizing the substantial heterogeneity among Latinos—including differences in national origin, immigration experiences, socioeconomic status, language, and race—is crucial, as oversimplification risks masking key disparities. To comprehensively understand these dynamics, the Task Force: Latino Researchers Against Cancer (TFLRAC) convened specialists in oncology, public health, and behavioral sciences to systematically examine the multiple influences contributing to these disparities. Findings highlight environmental hazards, genetic susceptibilities, cultural stigmas, and linguistic barriers as significant drivers. Systemic issues such as discrimination, colorism, inadequate healthcare coverage, workforce disparities, socioeconomic challenges, and underrepresentation in clinical trials further compound these inequities. Addressing these disparities requires a multifaceted strategy, including targeted research, culturally tailored interventions, and comprehensive policy reforms to improve healthcare access, workforce diversity, and clinical trial inclusion. Collaborative efforts across academia, healthcare systems, community organizations, governmental agencies, and industry partners are imperative to achieve equitable cancer outcomes among Latinos.